Dependent seniors clothing from the caregiver’s perspective - Caldas, Artemísia Lima (2014)
Seniors are in a time of relevant evidence, due to their extended life, result of different adopted procedures in the last years. In addition to the natural aging process other adversities affect them leading to dependence of some activities such as their dressing skills. We aim to offer, according to the caregivers’ perspective, suggestions of more adapted clothing, considering the dependent seniors real limitations in order to provide them more comfort and ease the handling by the caregiver.